Effectiveness of Corduk (Echinophora tenuifolia subsp. sibthorpiana) on safety and quality of kofte, a Turkish style meatball. Issue 1 (23rd August 2017) - Sengun, Ilkin Yucel; Yildiz Turp, Gulen; Kilic, Gulden; Sucu, Cisem
Abstract: In this research, the effect of Echinophora tenuifolia subsp. sibthorpiana (Corduk) on the inactivation of Salmonella Typhimurium in kofte (Turkish style meatball) was evaluated; as well as the quality characteristics of kofte (proximate composition, oxidation level, color parameters, microbiological, and sensory properties), during storage period at 4 °C for 7 days. Using Corduk at concentrations of 0.5, 1, and 1.5% in kofte was reduced the number of Salmonella cells in the range of 0.35–1.0 log cfu/g. The lowest total mesophilic aerobic bacteria count was obtained from kofte containing 1.5% of Corduk, after 7 days of storage. Corduk improved the color properties of kofte; hence, at the end of the storage period, samples containing 1 and 1.5% of Corduk significantly had higher scores than the control samples. The results of this study indicate that using Corduk in kofte could give an opportunity to improve the safety of meat products while improving the sensory characteristics. Practical applications: The natural substances from aromatic plants and spices can act as antimicrobial agents while improving quality attributes of the product. Kofte is a Turkish style meatball widely consumed in Turkey. This study was focused on the inclusion of Corduk into kofte formulation to improve the safety and quality of the product. Results indicate that Corduk can be considered as effective natural preservative for meat products without any adverse effect on the sensory quality.